Growth and Land Use with Agriculture and Industry - Zhang, Wei-Bin (Journal of Reviews on Global Economics, 2014)
This paper develops an economic growth model with economic structure and geography. The economy consists of one agricultural and one industrial sector and economic geography consists of urban and rural areas. The model synthesizes the main ideas in the Solow growth, the Alonso urban, and the von-ThÃ¼nen's agricultural models in a compact framework. We simulate the model. We demonstrate that the economic geography has a unique equilibrium point with the specified parameter values. We examine changes in the preference, productivity, urban and regional amenities, transportation conditions, the population, and land endowment upon the long-term economic growth, structure, and geography.